2011
DOI: 10.1007/s12519-011-0318-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics and meteorological factors of childhood Mycoplasma pneumoniae pneumonia in Hangzhou

Abstract: This study showed that the MPP rate was higher in older children than in younger ones. Girls had a higher positive rate of MPP than boys. In Hangzhou, MPP was more prevalent in summer and autumn. Air temperature was the only meteorological factor affecting the prevalence of MPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 20 publications
7
22
0
Order By: Relevance
“…During the entire period, the changes in the annual cycle of positive rates were irregular, with peaks in early summer (in 2012), mid-summer (in 2013), and early autumn (in 2014). This is in line with reports describing more M. pneumoniae infections with increased relative humidity and ambient temperature (19,20). In our neighborhood areas, recent epidemic outbreaks of M. pneumoniae infections were also noted in South Korea from 2010 to 2011, in Japan from 2011 to 2012, and in Beijing and Shanghai, China, in 2012 (4,21,22).…”
Section: Discussionsupporting
confidence: 93%
“…During the entire period, the changes in the annual cycle of positive rates were irregular, with peaks in early summer (in 2012), mid-summer (in 2013), and early autumn (in 2014). This is in line with reports describing more M. pneumoniae infections with increased relative humidity and ambient temperature (19,20). In our neighborhood areas, recent epidemic outbreaks of M. pneumoniae infections were also noted in South Korea from 2010 to 2011, in Japan from 2011 to 2012, and in Beijing and Shanghai, China, in 2012 (4,21,22).…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study show a similar, albeit less evident, cycle from 2000 to 2009, which could be associated with differences in the region, time and detection methods of the study. The annual incidence of MPP showed a gradually increasing trend from 16.9 to 31.9% in this study, which is similar to that reported in other studies (27,28). The age distribution of MPP in the present study was also comparable to the age-related increase reported in the literature (1,5,7).…”
Section: Discussionsupporting
confidence: 91%
“…Mycoplasma pneumoniae (MP) is an extracellular pathogen that attaches to ciliated epithelial cells of the respiratory tract mucosa and causes damage [1, 2]. MP infection is the dominant cause of pneumonia in children [36], who present with more than 40% of community-acquired pneumonia [7–9].…”
Section: Introductionmentioning
confidence: 99%